Synthesis of realistic and postmodern artistic techniques in modern literature (based on the works of V. Pelevin and Ulugbek Hamdam) - Oripova, Nigina Nishod qizi; Babaeva, Shoira Baymuradovna (The Lingua Spectrum, 2026)
The article examines the synthesis of realistic and postmodern artistic techniques in contemporary literature based on the works of Viktor Pelevin and Ulugbek Hamdam. The study focuses on the interaction between realism and postmodern aesthetics in literary texts. Special attention is given to intertextuality, meta‑narrative structures, simulation of reality, and game poetics. Th e research demonstrates that modern literature increasingly combines different aesthetic strategies, creating hybrid narrative forms. The article analyzes the configurations of synthesis in V. Pelevin’s prose based on six key novels (1996-2020). The main types identified are: realistic scene with metaphysical rupture; simulacrization of everyday life; play with document and mass media discourse. Reader effects include: ontological uncertainty, satirical demythologization, and aesthetic provocation.